Media Pembelajaran Interaktif Berbasis Canva untuk Meningkatkan Kreativitas Siswa pada Mata Pelajaran Informatika di SMA - Alamsyah; Muslim; Ikhwannul Muslimin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The rapid development of digital technology has encouraged the use of interactive learning media to support students' creativity as one of the essential 21st-century skills. However, the learning process in Informatics at SMAN 1 Donggo is still dominated by lecture-based instruction, and the use of digital learning media has not been optimized, resulting in students' creativity not being fully developed. This study aimed to analyze the effect of Canva-based interactive learning media on students' creativity in Informatics at SMAN 1 Donggo, Bima Regency. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 56 students, including 28 students in the experimental class and 28 students in the control class, selected through purposive sampling. Data were collected using a creativity questionnaire that had met validity and reliability requirements. Data analysis included descriptive statistics, normality test, homogeneity test, Mann–Whitney U test, and N-Gain analysis using IBM SPSS Statistics. The results showed that the mean creativity score of the experimental class increased from 59.29 to 86.79, while the control class increased from 49.82 to 54.82. The experimental class achieved an N-Gain score of 67.08% (moderate to high category), whereas the control class obtained 16.20% (low category). The Mann–Whitney U test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between the two groups. Therefore, Canva-based interactive learning media were proven to have a significant and effective impact on improving students' creativity in Informatics and can serve as an alternative learning medium to support 21st-century education.